Classes of Drugs that Mitigate Radiation Syndromes - Micewicz, Ewa D.; Damoiseaux, Robert D.; Deng, Gang; Gomez, Adrian; Iwamoto, Keisuke S.; Jung, Michael E.; Nguyen, Christine; Norris, Andrew J.; Ratikan, Josephine A.; Ruchala, Piotr; Sayre, James W.; Schaue, Dörthe; et al. (Frontiers in Pharmacology, 2021)
We previously reported several vignettes on types and classes of drugs able to mitigate acute and, in at least one case, late radiation syndromes in mice. Most of these had emerged from high throughput screening (HTS) of bioactive and chemical drug libraries using ionizing radiation-induced lymphocytic apoptosis as a readout. Here we report the full analysis of the HTS screen of libraries with 85,000 small molecule chemicals that identified 220 “hits”. Most of these hits could be allocated by maximal common substructure analysis to one of 11 clusters each containing at least 3 active compounds. Further screening validated 23 compounds as being most active; 15 of these were cherry-picked based on drug availability and tested for their ability to mitigate acute hematopoietic radiation syndrome (H-ARS) in mice. Of these, 5 bore a 4-nitrophenylsulfonamide motif while 4 had a quinoline scaffold. All but two of the 15 significantly (P<0.05) mitigated H-ARS in mice. We had previously reported that the lead 4-(nitrophenylsulfonyl)-4-phenylpiperazine compound (NPSP512), was active in mitigating multiple acute and late radiation syndromes in mice of more than one sex and strain. Unfortunately, the formulation of this drug had to be changed for regulatory reasons and we report here on the synthesis and testing of active analogs of NPSP512 (QS1 and 52A1) that have increased solubility in water and in vivo bioavailability while retaining mitigator activity against H-ARS (P<0.0001) and other radiation syndromes. The lead quinoline 057 was also active in multiple murine models of radiation damage. Taken together, HTS of a total of 150,000 bioactive or chemical substances, combined with maximal common substructure analysis has resulted in the discovery of diverse groups of compounds that can mitigate H-ARS and at least some of which can mitigate multiple radiation syndromes when given starting 24 hours after exposure. We discuss what is known about how these agents might work, and the importance of formulation and bioavailability.